2022
DOI: 10.3390/vetsci9100535
|View full text |Cite
|
Sign up to set email alerts
|

Vet-OncoNet: Malignancy Analysis of Neoplasms in Dogs and Cats

Abstract: Analysis of canine and feline tumor malignancy data can help clinicians identify high-risk patients and make more accurate decisions. Based on a sample of 16,272 cancer records, including 3266 cats and 13,006 dogs, collected from January 2019 to December 2021 in the Vet-OncoNet Network database, this study aimed to compare the tumor malignancy profile between cats and dogs, considering animal-related factors (sex, age, and breed), topography, and geographic location using a mixed-effects logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
3
9
1
Order By: Relevance
“…In accordance with previous studies, female dogs showed higher overall tumor numbers [ 5 , 6 , 8 , 17 , 18 , 20 , 22 ] and IRs [ 4 , 9 11 ] compared to male dogs (IR: 850 vs. 679, respectively), and a higher IRR for malignant tumors ( Table 6 ). These results may be partly influenced by relatively high numbers of tumors in the mammary gland.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with previous studies, female dogs showed higher overall tumor numbers [ 5 , 6 , 8 , 17 , 18 , 20 , 22 ] and IRs [ 4 , 9 11 ] compared to male dogs (IR: 850 vs. 679, respectively), and a higher IRR for malignant tumors ( Table 6 ). These results may be partly influenced by relatively high numbers of tumors in the mammary gland.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of benign tumors was higher than that of malignant tumors (54.91% versus 45.09%, respectively), as reported in most previous studies in dogs [ 4 6 , 9 , 11 , 16 , 18 , 23 ], but different from a Japanese [ 21 ] and two Italian [ 8 , 10 ] studies, which reported 57.5%, 53%, and 51% of all tumors as malignant, respectively. The percentage of benign tumors may generally be underestimated due to less frequent pathological assessment.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The most frequent cancer in dogs is a mammary tumour; about half of these cancers are malignant 1 . Surgical resection is the preferred treatment for mammary gland neoplasia, and radiotherapy and chemotherapy are used as adjuvant therapies to surgery 2 . Major issues with cancer treatment that restrict the amount of chemotherapeutic drugs are drug toxicity and the emergence of drug resistance 3 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Certain breeds are believed to be at risk for specific neoplasia, which is thought to arise due to inadvertent selection of genetic mutations predisposing to cancer, along with the selection of specific genetic traits. [4][5][6][7] Early detection of cancer is desirable because it may reduce the need for aggressive treatment and the incidence of metastasis. In addition, it may improve…”
mentioning
confidence: 99%